RESPON BEBERAPA GALUR TOMAT (Lycopersicum esculentum Mill.) TERHADAP PENYAKIT BUSUK DAUN (Phytophthora infestans (Mont.) de Bary) - Gungun Wiguna; Rahmat Sutarya; Yenny Muliani (Universitas Wahid Hasyim, 2015)
Tomato varieties cultivated in Indonesia is still susceptible to late blight. This research aims to determine the level of resistance of some strains of tomato to late blight. The research was conducted at the field trial Indonesian Vegetable Research Institute Lembang located at an altitude of ± 1250 above sea level. The type of soil Andisol temperate type B, with a daily average temperature ranging between 19-24 ° C, relative humidity ranged between 34-90% and an average rainfall of 2207.5 mm/year. The research was conducted from March to May 2015. The studies used randomized complete block design (RCBD) with 16 treatment lines/varieties consisting of 15 strains of balitsa tomato germplasm collection and the commercial varieties called